4x+6+3x+4=(-40)+4

Simple and best practice solution for 4x+6+3x+4=(-40)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+6+3x+4=(-40)+4 equation:


Simplifying
4x + 6 + 3x + 4 = (-40) + 4

Reorder the terms:
6 + 4 + 4x + 3x = (-40) + 4

Combine like terms: 6 + 4 = 10
10 + 4x + 3x = (-40) + 4

Combine like terms: 4x + 3x = 7x
10 + 7x = (-40) + 4
10 + 7x = -40 + 4

Combine like terms: -40 + 4 = -36
10 + 7x = -36

Solving
10 + 7x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 7x = -36 + -10

Combine like terms: 10 + -10 = 0
0 + 7x = -36 + -10
7x = -36 + -10

Combine like terms: -36 + -10 = -46
7x = -46

Divide each side by '7'.
x = -6.571428571

Simplifying
x = -6.571428571

See similar equations:

| 3z-836=-77 | | Y+8=2y-4 | | -3x+10=94+4x | | 5y^2-7y=-2 | | 27=3(2x-7) | | -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) | | 4m=m+21 | | 20x^2-25+5= | | -2=4r-s | | 4(j-3)=23-3j | | 2x+5(x-18)=-174 | | 90=-8y+50 |

Equations solver categories